Renewable energy technology diffusion model: Evaluation of financial incentives in the electricity market of ecuador - Fran Zhovani Reinoso-Avecillas; Faustino Moreno-Gamboa; César Nieto-Londoño (International Journal of Thermofluids)
This paper develops a simulation model using the System Dynamics paradigm to evaluate the effect of applying financial incentives on the diffusion of non-conventional renewable energy technologies in the Ecuadorian electricity market. The barriers to the diffusion of renewable energies are studied, the diffusion models are characterised, and the model is built with market variables and financial indicators integrated into its base structure. The Ecuadorian electricity market is described as a case study focusing on the incentive scheme. Based on investment, generation, and indirect incentives, this scheme plays a crucial role in promoting renewable energy technologies. Different long-term diffusion scenarios are simulated and compared with each other and with the baseline scenario to obtain diffusion rates and financial information for five renewable generation technologies: non-conventional hydro, wind, solar photovoltaic, biomass, and geothermal. The results of the simulations show that the combination of incentives leads to high diffusion rates, reassuring the audience about the potential impact of the proposed model. However, the feed-in tariff and tradable green certificate incentives are the most effective in promoting the use of renewable energy. For the Ecuadorian electricity market, the results show that wind and biomass technologies would be the most profitable, as opposed to geothermal energy, whose diffusion will not be feasible within the simulated period.